2021
DOI: 10.3390/biom11091281
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon as a Therapeutic Approach to Severe Hypoglycemia: After 100 Years, Is It Still the Antidote of Insulin?

Abstract: Hypoglycemia represents a dark and tormented side of diabetes mellitus therapy. Patients treated with insulin or drug inducing hypoglycemia, consider hypoglycemia as a harmful element, which leads to their resistance and lack of acceptance of the pathology and relative therapies. Severe hypoglycemia, in itself, is a risk for patients and relatives. The possibility to have novel strategies and scientific knowledge concerning hypoglycemia could represent an enormous benefit. Novel available glucagon formulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 129 publications
(153 reference statements)
0
9
1
1
Order By: Relevance
“…Ready-to-use glucagon products, including injectable liquid glucagon (Gvoke; Xeris Pharmaceuticals) 18 and nasal dry powder glucagon (Baqsimi; Lilly), 19 offer easier administration and have similar safety and efficacy profiles to those of pre-existing GEKs. 8 Dasiglucagon (Zegalogue; Zealand Pharma) is the first glucagon analogue available in a ready-to-use aqueous formulation. Its altered chemical structure improves its physical and chemical stability, providing improved longterm stability in aqueous solution and allowing dasiglucagon to be stored in a prefilled syringe and autoinjector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ready-to-use glucagon products, including injectable liquid glucagon (Gvoke; Xeris Pharmaceuticals) 18 and nasal dry powder glucagon (Baqsimi; Lilly), 19 offer easier administration and have similar safety and efficacy profiles to those of pre-existing GEKs. 8 Dasiglucagon (Zegalogue; Zealand Pharma) is the first glucagon analogue available in a ready-to-use aqueous formulation. Its altered chemical structure improves its physical and chemical stability, providing improved longterm stability in aqueous solution and allowing dasiglucagon to be stored in a prefilled syringe and autoinjector.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Many people with diabetes often do not recognize mild hypoglycaemic events or, in the case of SH, they are often reluctant to discuss these episodes with their healthcare providers for a number of reasons (including work issues, driving certification, and others). 7,8 In people with T1D or T2D, SH episodes are associated with several adverse health outcomes, including cardiac dysfunction and sudden death, 9 as well as non-cardiac conditions, such as impaired cognitive function and seizures. 10 Glucagon is a first-line emergency treatment for SH.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon has long been considered a candidate therapy for the treatment of hypoglycaemia because of its role in glucose homeostasis via glycogenolysis and gluconeogenesis. 1 Based on this role in glucose metabolism, glucagon has been proposed as a therapeutic agent for chronic hypoglycaemic diseases such as congenital hyperinsulinism 2 and postbariatric hypoglycaemia. 3 Recent studies have also shown that glucagon plays a central role in the regulation of lipid metabolism, energy expenditure and satiety regulation, 4 which implies that it may have a potential role in obesity management; this theory is supported by the fact that glucagon displays co-agonism with glucagon-like peptide-1 (GLP-1).…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon has long been considered a candidate therapy for the treatment of hypoglycaemia because of its role in glucose homeostasis via glycogenolysis and gluconeogenesis 1 . Based on this role in glucose metabolism, glucagon has been proposed as a therapeutic agent for chronic hypoglycaemic diseases such as congenital hyperinsulinism 2 and postbariatric hypoglycaemia 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Marrano, N. and his research group described similarities between GLP-1 and irisin, a myokine released in response to a high-fat diet and exercise focusing attention on the role of the gut, muscle and endocrine pancreas network on energy control [ 12 ]. Porcellati, F. et al described the pathophysiological mechanisms of hypoglycemia and summarized the most recent advances in glucagon therapy, especially focusing on a new nasal formulation [ 13 ]. The authors hypothesize a new possible action of nasal glucagon administration in the brain and, as a consequence, in hepatic glucose release.…”
mentioning
confidence: 99%